Analysis of Perumda Market Revenue Growth in Supporting Makassar City Post Covid-19 - Supiati, Supiati; Zainal, Henni (Pinisi Business Administration Review, 2023)
Market levies are a source of regional income which greatly contributes to the regional original income (PAD) of Makassar City. It can be proven that the Effectiveness ratio can reach the criteria of very effective, and effective, except in May the effectiveness ratio only reached the Effective ratio, this is caused by several factors including the limited facilities / services provided by the government, the number of traders who are actively selling, less than optimal billing and lack of awareness of traders in fulfilling their obligations. While the contribution ratio shows that the contribution of levies to regional original income (PAD) to Makassar City is very good, with an average contribution of 98.66%. which means that Perumda Pasar services to traders are considered very good. While the Growth Rate of Market Service Charges achieved during 2021 post-Covid - 19 was an average of 93.16% with Very Successful Criteria, which means that Market Service Charges during 2021 experienced very good growth in contributing to Regional Original Revenue (PAD) ) Makassar city.